Analisis Daya Saing Ekspor Kakao Indonesia di Pasar Malaysia - Anggraini Susanti; Ayudana Kezia; Rasidin Karo Karo Sitepu; Reyhani Intan Sabrina; Muhammad Akbar Husain; Desri Yohanna; Roby Andika; Nur Faizatul Luthfiah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Cocoa is a plantation crop that has a high contribution to the Indonesian economy through export activities. The large number of people interested in processed cocoa products means that demand for cocoa is increasing every year. The aim of the research carried out was to measure and see the level of comparative competitiveness of Indonesian cocoa in the main importing country, namely Malaysia. This research was conducted from March 2024 to April 2024. This research uses secondary data in the form of panel data for the period 2013-2022. The method used is Revealed Comparative Advantage (RCA) to measure and determine the level of competitiveness of Indonesian cocoa's comparative advantage. The research results show that Indonesian cocoa in the Malaysian market has strong competitiveness with an average RCA value of 2.61197. This also shows that Indonesian cocoa can compete in the global market by continuing to develop both technology and information.